Family Support and Compliance in Taking Medication Against the Elderly with Hypertension in the Work Area of Parongpong Health Center in West Bandung Regency - mersi nade (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
Increasing in age will be followed by changes in the organ system, especially among the elderly who will experience various health problems. One of them is hypertension. Hypertension is a degenerative disease that can be a silent killer. Therefore, hypertension management is needed for the elderly to avoid further complications. Management of hypertension can be done if there is family support, because the family is the closest person to the elderly. One of the family supports that can be given to help the elderly's daily living activity is to remind them to take hypertension medication regularly. The purpose of this study was to find a relationship between family support and medication adherence. The design of this research is descriptive, with cross sectional approach. The sampling was done using a purposive sampling technique. Data collection was conducted in Desa Karyawangi RT / RW 003/007, Kacamatan Parongpong, West Bandung Regency with 37 respondents, using a family support questionnaire and a Morisky 8-item Medication Adherence Questionnaire (MMAS-8) that was filled out by respondents. This study used the Spearmen test. The result showed 26 people (70.3%) received low family support, and as many as 25 people (67.6%) complied with taking hypertension medication. Statistical analysis showed that there was no relationship between family support and medication adherence (p value 0.748). The advice that can be given is for families of elderly people with hypertension to continue to provide support in reminding the elderly to take medication regularly. For further researchers, conducting research on other factors that can affect medication adherence. Keywords: Family Support; Hypertension; Medication Compliance; Elderly